Scientific Literacy Training for Student in SMP N 11 Magelang and SMP N 13 Magelang - Nuryunita Dewantari; Muhammad Daniel Fahmi Rizal (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Scientific literacy is a person's ability to understand science, communicate science, and apply scientific knowledge in solving problems encountered in everyday life. Scientific literacy is an important thing for students to have in facing increasingly rapid developments. The level of scientific literacy in Indonesia is still relatively low compared to other countries, one of the reasons is the lack of wise use of the convenience and sophistication of technology for productive activities (Fitriyani, et al., 2020). This is in line with the results of observations at the two partner schools are SMP N 11 Magelang and SMP N 13 Magelang, that the implementation of scientific literacy in the two partner schools is not optimal, so scientific literacy training is still needed for students. Based on these problems, the aim of this community service activity is to train students to understand scientific literacy and be able to apply it in everyday life. The method used in this activity is training (lectures and practice) involving students directly. This activity was carried out in 2 meetings for each partner school. First meeting providing material and the second meeting practicing scientific literacy questions. At the second meeting, apart from practicing questions, students were also asked to fill out a response questionnaire to the activities they had carried out. Based on the results of the questionnaire analysis, it is known that students feel happy and are motivated to learn science by participating in training activities, so it can be concluded that the activities were carried out well.